Get the Story Straight: Contextual Repetition Promotes Word Learning from Storybooks - Horst, Jessica S.; Parsons, Kelly L.; Bryan, Natasha M. (Frontiers in Psychology, 2011)
Although shared storybook reading is a common activity believed to improve the language skills of preschool children, how children learn new vocabulary from such experiences has been largely neglected in the literature. The current study systematically explores the effects of repeatedly reading the same storybooks on both young children's fast and slow mapping abilities. Specially created storybooks were read to 3-year-old children three times during the course of 1 week. Each of the nine storybooks contained two novel name–object pairs. At each session, children either heard three different stories with the same two novel name–object pairs or the same story three times. Importantly, all children heard each novel name the same number of times. Both immediate recall and retention were tested with a four-alternative forced-choice task with pictures of the novel objects. Children who heard the same stories repeatedly were very accurate on both the immediate recall and retention tasks. In contrast, children who heard different stories were only accurate on immediate recall during the last two sessions and failed to learn any of the new words. Overall, then, we found a dramatic increase in children's ability to both recall and retain novel name–object associations encountered during shared storybook reading when they heard the same stories multiple times in succession. Results are discussed in terms of contextual cueing effects observed in other cognitive domains.